Spatiotemporal Distribution and Clinical Characteristics of Zoonotic Tuberculosis, Spain, 2018–2022 - Álvaro Roy; Diana Gómez-Barroso; Elena Cruz-Ferro; Ana Fernández; Isabel Martínez-Pino; María del Henar Marcos; Isabel Ursúa-Díaz; Susana Miras; Nuria Echave; Evi Ounarou; Beatriz Romero; Laura Herrera-León; et al. (Emerging Infectious Diseases)
Zoonotic tuberculosis (zTB) is a communicable disease that has major effects on both human and animal health. Spain reports the highest number of zTB cases in humans annually in the European Union. We describe the epidemiology of human cases of zTB caused by Mycobacterium bovis and M. caprae in Spain during 2018–2022. The incidence of M. bovis infection compared with M. tuberculosis infection was higher in patients who were native-born (adjusted odds ratio [aOR) 2.32, 95% CI 1.44–3.82), HIV-negative (aOR 3.39, 95% CI 1.24–14.0), or had extrapulmonary forms of TB (aOR 2.20, 95% CI 1.46–3.28). The spatial pattern differed by M. tuberculosis complex species; we identified 3 significant clusters of M. bovis and 1 of M. caprae in bovine TB–free regions. Our results show the importance of including animal and human data on circulating zoonotic pathogens under the One Health umbrella.